The Impact of Gadget Nomophobia on Social Life of Adolescents in Medan City - Simatupang, Ray Dinho; Ivanna, Julia (Journal of Community Service For Indonesian Society, 2023)
This research was conducted in sub-districts that are suitable for nomophobia settlements in Medan City. The purpose of this study was to find out the social life of nomophobic teenagers in the social environment and to find out the positive and negative impacts of gadgets on teenagers. Subjects in this study amounted to 3 informants. Writing using descriptive qualitative method and analyzing data qualitatively and using the technique of taking the subject with the Snowball Sampling method. Data instruments in the form of in-depth interviews, observation and documentation. From the results of the research conducted, the researchers found that addicts who are addicted to gadgets or nomophobia have a social life that leads to negative impacts and decreased levels of achievement due to not being able to divide time between playing gadgets and being responsible. students and children in the household. The essence of this research is that there are more negative impacts on teenagers who are addicted to gadgets than the positive impacts caused by adolescent nomophobia.